2023
DOI: 10.3390/ijerph20054548
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Rural and Remote Australian General Practitioners’ Involvement in High-Acuity Patients

Abstract: This study aimed to understand the experiences, barriers, and facilitators of rural general practitioners’ involvement with high-acuity patients. Semi-structured interviews with rural general practitioners in South Australia who had experience delivering high-acuity care were audio-recorded, transcribed verbatim, and analyzed through content and thematic approaches incorporating Potter and Brough’s capacity-building framework. Eighteen interviews were conducted. Barriers identified include the inability to avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Even a modest reduction in patient transfers has the potential to result in significant savings for both individual patients and the healthcare system. As another incentive, research on attracting and retaining a rural workforce identified that clinical support was a significant factor for junior doctors [17,18]. Ensuring that rural locations are well equipped with POCUS as a diagnostic tool may help provide additional support for junior doctors, thus helping to address rural workforce issues.…”
Section: Discussionmentioning
confidence: 99%
“…Even a modest reduction in patient transfers has the potential to result in significant savings for both individual patients and the healthcare system. As another incentive, research on attracting and retaining a rural workforce identified that clinical support was a significant factor for junior doctors [17,18]. Ensuring that rural locations are well equipped with POCUS as a diagnostic tool may help provide additional support for junior doctors, thus helping to address rural workforce issues.…”
Section: Discussionmentioning
confidence: 99%
“…Other than the negatives from the pandemic response, some positives do emerge. Tese include the improved uptake of virtual healthcare [17], expanded and extended scope of health professional practice [18][19][20][21], appropriate planning and resourcing of essential services [22,23], the importance of engaging with consumers, and appropriate culturally and linguistical public health approaches to underserviced communities [24][25][26][27][28]. Troughout the COVID-19 pandemic, rapid systematic reviews were conducted to synthesize evidence to inform the decision-making by public leaders.…”
Section: Introductionmentioning
confidence: 99%